Humeral elevation reduces the dynamic control ratio of the shoulder muscles during internal rotation. Issue 4 (April 2017) - Howard, William; Burgess, Jonathan; Vrhovnik, Borut; Stringer, Christian; Choy, Sherrie T.; Marsden, Jonathan F.; Gedikoglou, Ingrid A.; Shum, Gary L.
Abstract: Objectives: To determine the differences in the dynamic control ratio of the glenohumeral joint rotators, during internal rotation at 20° and 60° of humeral elevation in the scapular plan. Dynamic control ratio (DCR) is defined as the ratio between eccentric action of the lateral rotators and the concentric action of the medial rotators. Design: A cross-sectional laboratory study. Methods: Thirty asymptomatic participants (men n = 14, women n = 16, mean age = 29.4 ± 8.9 years, BMI: 24.1 ± 5.4) were tested. Peak torque generated by the concentric action of the MR and the eccentric action of the LR of the shoulder joint and the DCR were evaluated on the dominant arm using an isokinetic dynamometer at 20° and 60° of humeral elevation at a speed of 20°/s. Results: There was a significant decrease in the DCR at 60° humeral elevation when compared to 20° humeral elevation (p < 0.05). This decrease was due to the significant decrease in eccentric peak torques at 60° humeral elevation when compared to 20° (p < 0.05). However, there was no significant difference in the concentric peak torques between 20° and 60° (p > 0.05). Conclusions: The significant decrease in the DCR as a consequence of a decrease in the eccentric peak torque of the LR when the humerus is in a more elevated position suggests that the introduction of humeral elevation can be used as a progression for improving the eccentric action of the shoulder LR and subsequently the dynamic control of the shoulder.